2002
DOI: 10.1039/b206342e
|View full text |Cite
|
Sign up to set email alerts
|

DFT studies on the pairing abilities of the one-electron reduced or oxidized adenine–thymine base pair

Abstract: Using density functional theory (DFT), the hydrogen bonds making up the adenine-thymine (A-T) base pair are found to increase in total energy upon one-electron oxidation or reduction by 10.9 and 13.3 kcal mol À1 , respectively. Due to unsymmetric changes in the H-bond lengths, this strengthening affects an expansion of the base pair length (N1 0 -N9) by $0.27 A ˚. In the oxidized pair, A + -T, deprotonation from N 6 , and with the reduced pair, A À -T, protonation on N3 or N7 lead to base pairs which have simi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
85
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(92 citation statements)
references
References 65 publications
7
85
0
Order By: Relevance
“…Therefore, we suggest that the covalent bond would be formed via the oxygen atom of the guanine moiety. Indeed, it has been shown that the guanine radical cation deprotonates on nitrogen 1 [48][49][50] and leads to a radical mainly located on the oxygen atom of the guanine. [51][52][53][54][55] Figure 7 shows the two resulting putative structures of the photoadducts in agreement with all the above-mentioned data.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we suggest that the covalent bond would be formed via the oxygen atom of the guanine moiety. Indeed, it has been shown that the guanine radical cation deprotonates on nitrogen 1 [48][49][50] and leads to a radical mainly located on the oxygen atom of the guanine. [51][52][53][54][55] Figure 7 shows the two resulting putative structures of the photoadducts in agreement with all the above-mentioned data.…”
Section: Discussionmentioning
confidence: 99%
“…In Nocker et al work [331] hydrogen bonds are calculated by development of a more general method avoiding lots of restraints basing on the supramolecular approach and use of Density Functional Theory (DFT), a well-established method when dealing with this type of interactions [332][333][334][335][336][337][338], that in comparison with force-field derived hydrogen bond energies points out an underestimation of those in all studied force fields [339]. DFT expresses the electronic energy of a system in terms of its density [340] instead of using the many-electronic wave function and depends on the knowledge of the exchange correlation energy functional for which different approximations can be used [341].…”
Section: Calculation Of Hydrogen Bonds Characteristicsmentioning
confidence: 99%
“…[12,13] The binding of anions to neutral receptors is of special significance; first, to avoid the competing counterion complexes present if cationic hosts are used, and second, the selectivity is highest in neutral receptors due to the dominance of directional interactions. [14] The neutral anion binding receptors can be divided into two classes: receptors that bind anions by hydrogen bonding and receptors that coordinate anions at the Lewis acidic center of a neutral organometallic ligand. The favorable interaction of anions with electron-deficient aromatic rings can be applicable to the design of a new family of neutral anion receptors.…”
Section: Methodsmentioning
confidence: 99%
“…In solution, protonation on N3 or N7 of the adenine anion by a nearby water molecule is likely to occur. [14] In the case of RNA, adenine protonation is serious as it may lead to loss of selectivity in base-pairing such that adenine can pair with both uracil and cytosine. [14] In the present experiment there is no water present.…”
mentioning
confidence: 99%
See 1 more Smart Citation